Effects of medication intake on the risk of hemorrhage in patients with sporadic cerebral cavernous malformations - Chen, Bixia; Lahl, Kirstin; Saban, Dino; Lenkeit, Annika; Rauschenbach, Laurèl; Santos, Alejandro N.; Li, Yan; Schmidt, Boerge; Zhu, Yuan; Jabbarli, Ramazan; Wrede, Karsten H.; Kleinschnitz, Christoph; et al. (Frontiers in Neurology, 2023)
Objective Recurrent intracerebral haemorrhage (ICH) poses a high risk for patients with cerebral cavernous malformations (CCMs). This study aimed to assess the influence of medication intake on haemorrhage Methods From a database of 1409 consecutive CCM patients (2003-2021), subjects with sporadic CCMs and complete magnetic resonance imaging data were included. We evaluated the presence of ICH as mode of presentation, occurrence of ICH during follow-up, and medication intake, including beta blockers, statins, antithrombotic therapy, and thyroid hormones. The impact of medication intake on ICH at presentation was calculated using univariate and multivariate logistic regression with age- and sex-adjustment. The longitudinal cumulative 5-year risk for (re-)haemorrhage was analysed using Kaplan–Meier curves and Cox regression. Results A total of 1116 CCM patients were included. Logistic regression analysis showed a significant correlation (OR: 0.520, 95% CI: 0.284-0.951, p = 0.034) between antithrombotic therapy and ICH as mode of presentation. Cox regression analysis revealed no significant correlation between medication intake and occurrence of (re-)haemorrhage (hazard ratios: beta blockers 1.270 [95% CI: 0.703-2.293], statins 0.543 [95% CI: 0.194-1.526], antithrombotic therapy 0.507 [95% CI: 0.182-1.410], and thyroid hormones 0.834 [95% CI: 0.378-1.839]). Conclusions In this observational study, antithrombotic treatment was associated with the tendency to a lower rate of ICH as mode of presentation in a large cohort of sporadic CCM patients. Intake of beta blockers, statins, and thyroid hormones had no effect on haemorrhage as mode of presentation. During the 5-year follow-up period, none of the drugs affected the further risk of (re-)haemorrhage.